Reducing salt in bread: a quasi-experimental feasibility study in a bakery in Lima, Peru - Saavedra Garcia, Lorena (2015)
Objectives: To explore salt content in bread and to evaluate the feasibility of reducing salt contained in ‘pan francés’ bread. Design: The study had two phases. Phase 1, an exploratory phase, involved the estimation of salt contained in bread as well as a triangle taste test to establish the amount of salt to be reduced in ‘pan francés’ bread without detection by consumers. In Phase 2, a quasi-experimental, pre–post intervention study assessed the effects of the introduction of low-salt bread on bakery sales. Setting: A municipal bakery in Miraflores, Lima, Peru. Subjects: Sixty-five clients of the bakery in Phase 1 of the study; sales to usual costumers in Phase 2. Results: On average, there was 1·25 g of salt per 100 g of bread. Sixty-five consumers were enrolled in the triangle taste test: fifty-four (83·1 %) females, mean age 58·9 (SD 13·7) years. Based on taste, bread samples prepared with salt reductions of 10 % (P = 0·82) and 20 % (P =0·37) were not discernible from regular bread. The introduction of bread with 20 % of salt reduction, which contained 1 g of salt per 100 g of bread, did not change sales of ‘pan francés’ (P=0·70) or other types of bread (P =0·36). Results were consistent when using different statistical techniques. Conclusions: The introduction of bread with a 20 % reduction in salt is feasible without affecting taste or bakery sales. Results suggest that these interventions are easily implementable, with the potential to contribute to larger sodium reduction strategies impacting the population’s cardiovascular health.